Na Kung Kung: Nori Dari Bahan Lokal Dengan Rasa Lele Sebagai Inovasi Bisnis - Nadella Ervietasari (Journal Science Innovation and Technology (SINTECH), 2021)
Nori is a typical Japanese food in the form of thin sheets made from Porphyra seaweed. This type of seaweed is only found in sub-tropical countries, so it is not found in Indonesia. Nori consumed is still imported from abroad and the price is relatively expensive. One of the plants that can be used as raw material for nori is kale. Kale plants thrive and the price is cheap. The leaves contain antioxidants, 2.35% protein, 0.55% fat, 6.02% carbohydrates, and 1.04% crude fiber. The author's team added catfish as a flavoring because this fish has a low price and has high protein, rich in leucine and lysine. We call our products by the name of Na Kung Kung; as an innovative effort to replace the raw material for making nori with local ingredients that are widely available in Indonesia. The research method was carried out by organoleptic test. Through literature studies from various references, such as research journals, books, and data from the Ministry of Health of the Republic of Indonesia to obtain conclusions. The results showed that nori from kale with drying treatment for up to 12 hours with the addition of 1% carrageenan almost resembled commercial nori and was the most preferred based on organoleptic tests. The conclusion is that kale can be used as an alternative material for making nori. The existence of Na Kung Kung products is expected to increase the income of the Indonesian people during the Covid-19 pandemic.